Covid-19 and the youth-to-adult unemployment gap - Francesco Pastore (IZA World of Labor, 2023)
The Covid-19 pandemic has produced unprecedented negative effects on the global economy, affecting both the demand and supply side. Its consequences in terms of job losses have been important in many European countries. A large number of firms have been forced to dismiss at least part of their workforce or to close down all together. Considering that young people are usually penalized more than their adult counterparts during economic crises due to the so-called "last-in-first-out" principle, it is worthwhile to evaluate if the youth will also end up paying the highest price during this pandemic-induced recession.
Keywords: J6; J1; 330; youth unemployment rate; youth disadvantage; pandemic recession; Covid-19